THE BUSINESS JUDGMENT RULE (PART 2) - Stephen Kennedy-Good; Lindi Coetzee (Obiter, 2022)
The business judgment rule entails that courts should not hold a director liable for a decision that produces poor results in the circumstances in which the director made the decision in good faith, with care and on a informed basis, which the director believed was in the best interest of the company. This article considers the South African position relating to the director’s common law duty of care and skill. The Companies Act, recommendations of the King Committee, and the Department of Trade and Industry’s report on corporate law reform are taken into account. The efficiency of the current law in South Africa is evaluated in light of the advantages and disadvantages of the importation of a foreign legal rule. A closer examination of the characteristics of the business judgment rule and the South African law relating to director liability will reveal whether it is essential to implement the rule in South Africa. In paragraph 3 a conclusion is drawn and an assessment made of whether it is indeed desirable or necessary to import the business judgment rule into South African law.